2010
DOI: 10.1080/13811118.2010.524054
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to High-Lethality Suicide Attempts in Individuals with Borderline Personality Disorder

Abstract: The purpose of this study was to develop and test a model of high-lethality suicide attempts (HLSA) in individuals with Borderline Personality Disorder (BPD). An increased number of prior suicide attempts, substance use immediately prior to the attempt, and objective planning were proposed to lead directly to a HLSA, while aggression and impulsivity were hypothesized to lead indirectly to a HLSA through their associations with prior attempts. Path analysis revealed a revised model in which impulsivity was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 88 publications
(124 reference statements)
3
31
1
5
Order By: Relevance
“…Borderline personality disorder surely increases the risk of attempted suicide, but the relation with the lethality of such attempts is unclear. According to some studies, the lethality of suicide attempts committed by borderline patients results from an interaction between impulsivity (Chesin, Jeglic, & Stanley, 2010) and violent-aggressive features (McGirr, Paris, Lesage, Renaud, & Turecki, 2007), but other studies have ascertained that the presence of impulsive and aggressive traits is unrelated to the lethality of the suicidal behavior (Brodsky, Groves, Oquendo, Mann, & Stanley, 2006;Horesh, Orbach, Gothelf, Efrati, & Apter, 2003).…”
Section: Mental Disordersmentioning
confidence: 97%
“…Borderline personality disorder surely increases the risk of attempted suicide, but the relation with the lethality of such attempts is unclear. According to some studies, the lethality of suicide attempts committed by borderline patients results from an interaction between impulsivity (Chesin, Jeglic, & Stanley, 2010) and violent-aggressive features (McGirr, Paris, Lesage, Renaud, & Turecki, 2007), but other studies have ascertained that the presence of impulsive and aggressive traits is unrelated to the lethality of the suicidal behavior (Brodsky, Groves, Oquendo, Mann, & Stanley, 2006;Horesh, Orbach, Gothelf, Efrati, & Apter, 2003).…”
Section: Mental Disordersmentioning
confidence: 97%
“…The corresponding risk was nearly threefold in patients whose PAU admissions were related to suicide attempt or suicidal ideation. Since non-suicidal self-harm has been suggested to function as a means to regulate emotions, relieve distress, and communicate with, or elicit help from, others (46), it has often been dismissed as manipulative and hence is considered less serious than suicide attempt (27,33). Therefore, findings from Study II related to the non-suicidal self-harm variable may support those from a previous study (97), which found no significant difference between the objective lethality of non-suicidal self-harm and that of suicide attempt.…”
Section: 3mentioning
confidence: 99%
“…Despite clinical guidelines (24), as well as BPD experts (25,26), have suggested that inpatient treatment has the potential to reinforce, rather than prevent, repetitive suicidal behaviour in BPD patients they are often admitted to psychiatric acute units due to suicide risk. Although a large proportion of selfharm in BPD patients is not suicidal and does not require somatic inpatient treatment, there is also a high prevalence of serious self-harm (27) and suicide (28) among individuals with BPD. Therefore, it can be reasonably assumed that BPD patients admitted to a psychiatric acute unit due to suicide risk would have an increased risk for self-harm-induced somatic admission after discharge from the psychiatric hospital.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patterns of personality currently associated with the risk of SA, i.e. antisocial [8] and borderline personality [9] and sensation seeking [10] , were studied. SA with and without AUD (SA-AUD+ and SA-AUD-) were compared.…”
Section: Aim Of the Studymentioning
confidence: 99%